A prospective study of nerve-sparing radical hysterectomy for uterine cervical carcinoma in Taiwan - Chih-Jen Tseng; Huang-Pin Shen; Yu-Hsiang Lin; Chung-Yuan Lee; Will Wei-Cheng Chiu (Taiwanese Journal of Obstetrics & Gynecology, 2012)
Objective: Surgical therapy for cervical carcinoma carries a significant risk of functional impairment to the bladder. This study evaluates the feasibility and complications of nerve-sparing radical hysterectomy (NRH) in Taiwan. Methods: Between March 2010 and March 2011, consecutive patients diagnosed with early stage cervical cancer (FIGO stage Ia2 to Ib1) and tumor size < 3 cm were recruited prospectively to undergo NRH or conventional radical hysterectomy (RH). Patients with histories of urinary stress incontinence or bladder dysfunction disease were excluded. A modified Tokyo nerve-sparing radical hysterectomy was performed. Results: A total of 30 patients were enrolled. Among these, 18 patients underwent NRH with successful bilaterally nerve-sparing procedures in 15 cases (83%), unilaterally nerve-sparing procedures in 2 cases (11%), and a failure in 1 case (6%). The indwelling catheter was removed on postoperative day 6. The mean±SD duration from operation to spontaneous voiding was 6.8±1.5 days for women who underwent NRH; the corresponding duration for women who underwent RH or failed NRH was 20.6±3 days. None of the patients who underwent NRH required intermittent catheterization. All 12 patients who underwent RH needed self-catheterization after discharge. There was a significant reduction in the incidence of postoperative self-catheterization (p<0.01) and bladder dysfunction (p<0.006). Average satisfaction score analyzed by the Likert-scale questionnaire was 4.5 for the NRH group and 1.9 for RH group (p<0.0001). Conclusions: We concluded that the new technique of NRH can reduce postoperative bladder dysfunctions.